Multilayer crack-free hybrid coatings for functional devices - Islam, S. (SPIE, 2016)
Porous acid catalyzed TiO2 single, SiO2-TiO2 hybrid, and TiO2/SiO2-TiO2/SiO2 multilayer coatings are synthesized and characterized for optical and electro-optical applications. The reflection value is reasonably reduced from the surface of the glass by integrating sol-gel based spin-coated single and multilayer thin films. Structurally, the films show uniform, crackfree, and porous nanofilms with good surface roughness of below 10 nm, which has potential for optical applications. Wide range tunability of refractive index (2.83 to 1.59) with more than 78% optical transparency is observed. The multilayered reflection profile is observed around 0.18%, so these coatings are desirable for optochemical functional devices.